Development and Validation of an Educational Booklet for The Healthy Eating Management of Diabetes Mellitus During Ramadan Fasting - Meirina Dwi Larasati; Dian Luthfita Prasetya Muninggar; Firmansyah Firmansyah (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: iabetics who decide on Ramadan fasting are at risk of complications such as hypoglycemia, hyperglycemia, ketosis, or dehydration. The strategy for prevention is to provide education about managing DM with healthy food intake, medication, and exercise during Ramadan fasting. Therefore, it is essential to develop the media to implement education.Research Methods: This research was a research and development method. The model used in developing an educational booklet consists of four stages: define, design, develop, and disseminate. The feasibility of growing media was analyzed by the content validity index (CVI) using I-CV and S-CVI to assess whether the item is relevant or not relevant to the index CVI>0,80. Research Result: Define is the first stage to analyze the need for media development; based on the results of an online survey of nutritionists, as many as 71% mentioned that there were no specific educational media on healthy eating management for DM during Ramadan fasting. Design and development of educational media include literature studies on healthy eating during Ramadan fasting for DM, containing food menus during Ramadan fasting—subsequent dissemination by assessment from experts and target subjects. The assessing subject's content validity index (CVI) was carried out using the I-CV and S-CVI. The average value of I-CV is 0.875, and the average value of S-CVI is 0.875, meaning that all parts of the content are relevant in providing information about healthy eating for DM during Ramadan fasting. The reliability test by the target subject obtained Cronbach's alpha value of 0.850 was reliable. Conclusion: This booklet can be used as an educational medium for pre-Ramadan education. Then, the researchers developed this booklet by considering and improving the booklet design, which was stated to be appropriate.